Initial Reports of the Deep Sea Drilling Project 1985
DOI: 10.2973/dsdp.proc.84.117.1985
|View full text |Cite
|
Sign up to set email alerts
|

Ash Layers from Deep Sea Drilling Project Leg 84: Middle America Trench Transect

Abstract: Three Leg 84 sites provided a good record of explosive volcanism onshore (in Central America). Ash layers and many ashy pods are interbedded in Recent to Oligocene strata. Evidence of the main periods of activity was noted in Recent to upper Pleistocene, Pliocene-Pleistocene, lower Pliocene to upper Miocene, lower Miocene, and upper Oligocene. Noticeable traces of older volcanism were found in upper Eocene strata.The chemical analyses of glass shards show a dacitic to rhyolitic composition with a low to modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…The deficit is due to hydration of glass in seawater (Sheidegger et al, 1978). Ninkovitch (1979) demonstrates that hydration in glass shards reaches a saturation point of 4-5% in 250,000 to 400,000 yr. Our recent studies on samples from DSDP Legs 67 (Cadet et al, 1982) and 84 (Pouclet et al, 1985) show that hydration occurs more rapidly and leads to a greater content in acidic glass (5-8%) than in basic glass (3-5%). However, the initial water content is unknown, and magmatic acidic glasses may be richer in H 2 O (5% for rhyolitic glass in the Osaka group in Japan; Yoshikawa, 1978).…”
Section: Geochemistry Methodsmentioning
confidence: 94%
“…The deficit is due to hydration of glass in seawater (Sheidegger et al, 1978). Ninkovitch (1979) demonstrates that hydration in glass shards reaches a saturation point of 4-5% in 250,000 to 400,000 yr. Our recent studies on samples from DSDP Legs 67 (Cadet et al, 1982) and 84 (Pouclet et al, 1985) show that hydration occurs more rapidly and leads to a greater content in acidic glass (5-8%) than in basic glass (3-5%). However, the initial water content is unknown, and magmatic acidic glasses may be richer in H 2 O (5% for rhyolitic glass in the Osaka group in Japan; Yoshikawa, 1978).…”
Section: Geochemistry Methodsmentioning
confidence: 94%
“…data). Previous studies (Scheidegger et al, 1978;Ninkovich, 1979;Cadet et al, 1982;Pouclet et al, 1985aPouclet et al, , 1985b showed that hydration occurs rapidly (less than 400,000 yr) to reach a saturation point of 4% to 5% in a transparent glass. Beyond this point, phyllitic secondary products developed into the glass.…”
Section: Significances Of Analytical Resultsmentioning
confidence: 99%
“…For example, in Central American deep-sea tephra (DSDP Legs 66, 67, and 84;Cadet et al, 1981Cadet et al, , 1982Pouclet et al, 1985a), the CAF displays a lower calc-alkaline character. This character ranges from -14 to -12.8 in early Miocene time and from -13.3 to-9.2 in mid-Miocene to Holocene time.…”
Section: Eocenementioning
confidence: 99%
See 2 more Smart Citations